Yophytta Exercise to Reduce Hypertension in Pregnant Women - Heni Wijayanti; Dyah Ayu Wulandari; Kenri Brianita (Universitas Karya Husada Semarang, 2023)
ABSTRACT Hypertension or high blood pressure due to pregnancy, namely hypertension that occurs due to or during pregnancy, usually occurs at the age of 20 weeks of gestation, which results in morbidity and mortality. Efforts to reduce blood pressure through complementary therapy in pregnant women with hypertension are Yophytta exercise. this study was intended to determine the effect of Yophytta exercise on reducing blood pressure in pregnant women with hypertension int the Paduraksa Health Center area. Methods : research is a quantitative study with a Quasi Experiment method with one group pre test and post test. A sample of 18 respondents using a purposive sampling technique in accordance with the inclusion criteria. The instrument used was Yophytta exercise SOP and the blood pressure observation sheet. Results : of the observations were analyzed using the Wilcoxon Signed Ranks Test. The results of the analysis showed a p value of 0.000 with 0.05, which means that there is a difference in the average blood pressure before and after being given Yophytta exercise. There is an effect of Yophytta exercise on reducing blood pressure in pregnant women with hypertension in the Paduraksa Health Center area. Yophytta exercise can reduce blood pressure in pregnant women with hypertension. Keywords: Yophytta exercise; blood pressure; pregnant women ABSTRAK Hipertensi atau tekanan darah tinggi akibat kehamilan, yaitu hipertensi yang terjadi karena atau selama kehamilan, biasanya terjadi pada usia kehamilan 20 minggu, yang mengakibatkan morbiditas dan mortalitas. Upaya penurunan tekanan darah melalui terapi komplementer pada ibu hamil hipertensi adalah senam Yophytta . Tujuan : untuk mengetahui pengaruh senam Yophytta terhadap penurunan tekanan darah pada ibu hamil dengan hipertensi di wilayah Puskesmas Paduraksa. Metode : penelitian ini merupakan penelitian kuantitatif dengan metode Quasi Experiment dengan one group pre test dan post test. Sampel sebanyak 18 responden dengan menggunakan teknik purposive sampling sesuai dengan kriteria inklusi. Instrumen yang digunakan adalah SOP senam Yophytta dan lembar observasi tekanan darah. Hasil : Hasil observasi dianalisis dengan Wilcoxon Signed Ranks Test. Hasil analisis menunjukkan nilai p sebesar 0,000 dengan 0,05 yang berarti ada perbedaan rata-rata tekanan darah sebelum dan sesudah diberikan senam Yophytta . Ada pengaruh senam Yophytta terhadap penurunan tekanan darah pada ibu hamil hipertensi di wilayah Puskesmas Paduraksa. Senam Yophytta dapat menurunkan tekanan darah pada ibu hamil dengan hipertensi. Kata Kunci: senam Yophytta ; tekanan darah; ibu hamil